Control of the plasma electrolytic oxidation process - Lazarev Denis; Fatkullin Azamat; Parfenov Evgeny; Shevtsov Arkady; Silin Ivan; Abdurahmanov Vadim (EPJ Web of Conferences)
The article is devoted to solving the problem of controlling the plasma electrolytic oxidation process used for applying protective coatings on aluminum alloys in the potentiostatic mode. The problem of measuring the unobservable parameters of the surface layer was solved by using indirect identification of the state system by informative statistical characteristics of the population of microdischarges. The automated control system structure is developed and the operation algorithm is proposed.